A política comercial setorial e os efeitos do Mercosul: uma análise entre fluxos liberalizados e não liberalizados - Diverio, Tamara Silvana Menuzzi (Universidade do Vale do Rio dos Sinos, 2025)
This study reassesses the impact of Mercosur on trade flows by combining established methods from the traditional gravity literature with recent Difference-in-Differences techniques that are robust to heterogeneity. The differential of the analysis lies in separating trade flows into specific categories: liberalized trade and non-liberalized trade. This distinction is important because Mercosur's trade policy is not uniform, since some products had their intra-bloc tariffs completely eliminated while others remained protected by tariff barriers. The general objective of the research is to analyze the impact of Mercosur's creation on trade flows considering the sectoral policies applied. The methodology combines approaches such as: the application of difference-in-differences robust to heterogeneity according to Nagengast, Rios-Avila, and Yotov (2024), sectoral analysis that differentiates liberalized from non-liberalized trade, simultaneous control of three fixed effects using the Poisson Pseudo Maximum Likelihood (PPML) estimator, and the inclusion of bloc expansions. The results show that Mercosur had a positive and significant impact on trade among its members in the analyses conducted, and non-liberalized trade showed the largest gains. This behavior suggests the presence of intra-bloc protection and trade externalities induced by regional integration itself. The research contributes to the literature by demonstrating that, although Mercosur has stimulated trade, selective protection compromises the bloc's economic efficiency and limits its potential for deeper integration, highlighting the need to rethink trade policies to promote more uniform liberalization and greater economic cohesion among member countries.
Keywords: Mercosul; Modelo gravitacional; Comércio internacional; Diferenças-em-diferenças; Política comercial; Integração regional; Mercosur; Gravity model; International trade; Difference-in-differences; Trade policy; Regional integration; ACCNPQ::Ciências Sociais Aplicadas::Direito